Human Best Practice Science Learning Model on Human Respiratory System Material - Hayu, Wiworo Retnadi Rias; Sondakh, Delfina Christie; Febriani , Regina (Islamic Journal of Integrated Science Education (IJISE), 2024)
The success of the learning process really depends on the teacher's teaching. The aim is to find out what learning models are usually used by a teacher and how to apply these models to the learning process. This research uses a qualitative interview and observation approach. The results of this research, the model that is often used is the project based learning model and interestingly the learning is carried out by making human respiratory system teaching aids which are affordable and interesting. In conclusion, teachers choose methods based on the complexity of the material and learning objectives, where theory is conveyed through discussions or lectures, while concrete concepts are understood through experiments.